Crystallization Regulation and Dual‐Defects Healing by Self‐Polymerization of Multifunctional Monomer Additives for Stable and Efficient CsPbBr3 Perovskite Solar Cells. Issue 3 (18th December 2022) - Jiao, Yujing; Yao, Xinpeng; Bao, Fanliang; Mao, Jingwei; Chen, Haiyan; Duan, Yanyan; Yang, Peizhi; Tang, Qunwei; He, Benlin
Abstract : The photovoltaic performance of perovskite solar cells (PSCs) is immensely related to the perovskite film quality, defect states density, and interfacial energy‐level alignment. Herein, a self‐polymeric monomer of N‐(hydroxymethyl) acrylamide (HAM) with CC, CO, and –NH multifunctional groups is introduced in the preparation of a CsPbBr3 film by a two‐step method to regulate the crystallization process and band structure and simultaneously passivate the dual‐ionic defects. The results show that the HAM monomer first undergoes a pre‐polymerization in the CsBr precursor aqueous solution after preheating to retard the crystallization of CsPbBr3, and subsequently a further polymerization occurs during the annealing of the perovskite film to load at grain boundaries and form the CO⋯Pb (Cs) Lewis acid–base coordination and N–H⋯Br hydrogen bonding. Consequently, a large‐grained CsPbBr3 film with low defect density and optimized band structure is fabricated to effectively suppress nonradiative recombination and accelerate carrier extraction and transport, delivering a champion power conversion efficiency of 9.05% for the HAM‐incorporated CsPbBr3 PSCs, which is much higher than 6.50% efficiency for the reference one. Furthermore, the unencapsulated device maintains over 92% of the initial efficiency after 30 days storage in air with 85% relative humidity or at 85 °C, exhibiting superior moisture and thermal durability. Abstract : The N‐(hydroxymethyl) acrylamide(HAM)‐incorporated CsPbBr3 perovskite solar cell fabricated by a two‐step method achieves a cutting‐edge power conversion efficiency of 9.05% with excellent humidity and thermal stability via quality and energy‐level alignment improvement and dual‐defects passivation of perovskite film by employing a self‐polymerization strategy of monomer additives with multifunctional groups.